"My brain feels like a browser with 100 tabs open": A longitudinal study of teachers' mental health and well‐being during the COVID‐19 pandemic. (1st August 2021) - Kim, Lisa E.; Oxley, Laura; Asbury, Kathryn
Abstract : Background: Teaching and caring for pupils during the COVID‐19 pandemic has been a challenge for many teachers, and its impact on teachers' mental health and well‐being (MHWB) should be of great national and international concern. Aim and participants: This study examines 24 primary and secondary school teachers' MHWB experiences across three time points (April, July, and November 2020) using longitudinal qualitative trajectory analysis. Method: We used a mixture of inductive and deductive coding, based on the Job Demands–Resources Model, to identify the job demands (aspects of the job that can be physically or psychologically costly) and job resources (aspects of the job that can buffer the effects of job demands and promote achievement and growth) teachers reported experiencing across the three time points. Results: Generally, teachers' MHWB seemed to have declined throughout the pandemic, especially for primary school leaders. Six job demands contributed negatively to teachers' MHWB (i.e., uncertainty, workload, negative perception of the profession, concern for others' well‐being, health struggles, and multiple roles) and three job resources contributed positively to their MHWB (i.e., social support, work autonomy, and coping strategies). Conclusions: Policymakers and practitioners can support teachers' MHWB by engaging in more collaborative communication and ensuring greater accessibility to sources of social support. These discussions and provisions will be crucial in supporting teachers, and thereby the educational system, both during and after the pandemic.